IMPLIKASI KEARIFAN LOKAL BAGI PENGELOLAAN TAMAN NASIONAL WASUR - Yarman .; Sambas Basuni; Rinekso Soekmadi (Media Konservasi, 2013)
Wasur National Park (WNP), located in Papua island, was one of national parks inhabited by native communities namely Marind Imbuti, Kanume, Marori Men Gey and Yeinan. They have lived within the area for generations and hold tradition rights upon the land within the national park.   The aim of this research was to identify informal regulations and local wisdom which could be adopted for managing Wasur National Park. This research was conducted within two months.  Data were collected  during April – May 2012 by performing literature study, direct observation and interview. The natives wisdoms were in the form of sasi tradition, wisdoms toward the sacred places, totemism, hunting and education system.  The implications for the management of WNP is the creation of regional regulations, zoning, law enforcement, cultivation of plants and animals ofnative communities’ totems, alternative natural resource utilization, community training and assistance which consider the presence and interest of the community itself. Keyword: implication, local  wisdom,  Wasur National Park, Management